Functional effects of phytate-degrading, probiotic lactic acid bacteria and yeast strains isolated from Iranian traditional sourdough on the technological and nutritional properties of whole wheat bread. (15th February 2020) - Fekri, Arezoo; Torbati, Mohammadali; Yari Khosrowshahi, Ahmad; Bagherpour Shamloo, Hasan; Azadmard-Damirchi, Sodeif
Highlights: Sourdough fermentation in bread preparing is a main traditional method. Arasbaran traditional and native sourdough was investigated. Probiotic properties and phytate degrading ability were investigated. The sourdough microbiota was molecularly identified. Using combined yeasts and bacteria can be recommended for preparing sourdough. Abstract: The lactic acid bacteria (LAB) and yeast strains with phytate degrading ability were isolated from Iranian traditional sourdough, and based on the acid and bile tolerance, three LAB and three yeast strains were selected and molecularly identified. In this study, baker's yeast ( Saccharomyces cerevisiae ) was considered as a positive control strain to investigate the nutritional and technological properties of the isolated strains. All of the identified microorganisms were characterized based on additional probiotic properties and were evaluated for nutritional and technological characteristics. The functional features are associated with degradation of phytate, antioxidant capacity, exopolysaccharides, phenolic compound content and in vitro starch digestion. Among all the tested strains the highest amount of phytase production capacity (1.64 Unit/ml) and lowest phytate content (17.49 mg/5 g) belonged to Kluyveromyces marxianus . According to the results, the bread prepared by using Kluyveromyces aestuarii possessed the highest porosity percentage (70.43%), and the lowest hardness (508.71 g).